СИСТЕМ ИЗУЗЕТАКА ПРИМЕНЕ «ТЕОРИЈЕ ПЛОДА ОТРОВНОГ ДРВЕТА» - Feješ, Ištvan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The work is divided into five chapters. In the introduction, the author emphasizes that the issue of illegal evidence, especially the over-effect of the excluded evidence, one of the most complex problems of modern theory and practice of criminal proceedings. The second chapter deals with the general issues of illegal evidence. The third chapter summarizes the fruit of poisonous tree doctrine.Autor emphasizes that American jurisprudence has built a number of exceptions which seeks to limit the effects of rigidity and strictness of this theory. Chapter four is the central part of the work and is dedicated to the processing of exceptions to the fruit of poisonous tree doctrine. The fifth chapter is the conclusion to which the author notes that instead the fruit of poisonous tree doctrine in contemporary American jurisprudence almost exclusively exceptions apply and that its practical importance is far lower than most European theorists considered. pan>поступка и ефикасно сузбијање криминалитета. Америчка судска пракса је нашла решење у «теорији плода отровног дрвета», али је изградила и систем изузетака, о којима континентални правници мало говоре,а сврха им је избегавање незгодних последица њене строгости, крутости и неселективности али уједно и у битној мери ограничавају њену примену у пракси.Они су у центру пажње овог рада. ка од fruit of poisonous tree doctrine. Пето поглавље је закључак у коме писац констатује да се уместо саме fruit of poisonous tree doctrine у савременој америчкој судској пракси скоро искључиво примењују изузеци и да је њен практични значај данас далеко мањи него што већина европских теоретичара сматра.